Serum Calcium, Phosphate and Ferritin Level in Adult Male Patients with Transfusion Dependent Thalassemia - Urmi, S F H; Begum, Shelina; Munira, Fatema Tuz; Das, Kamol Chandra (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Thalassemia is an inherited blood disorder characterized by decreased hemoglobin production resulting in anemia. Patients with transfusion dependent thalassemia (TDT) develop iron overload due to regular blood transfusion. This excess iron is deposited in the tissue and causes organ failure which may lead to hypocalcaemia and hyperphosphatemia. This study was done to measure serum total calcium, serum inorganic phosphate and serum ferritin levels in adult male patients with TDT. This cross sectional study was carried out from 01 March 2018 to 28 February 2019 in Bangabandhu Sheikh Mujib Medical University, Dhaka. Thirty five consecutive male patients with TDT of 18 to 40 year were selected from the outpatient department (OPD) of Transfusion Medicine and Hematology. For comparison, 35 age matched apparently healthy male subjects were selected on the basis of selection criteria. Serum total calcium, serum inorganic phosphate, serum ferritin, serum albumin, serum alkaline phosphatase and serum creatinine levels were measured by colorimetric method using automated analyzer. For statistical analysis independent sample t-test was done using SPSS version 16. Serum total calcium level was significantly (p<0.001) lower, serum inorganic phosphate and serum ferritin level was significantly (p<0.001) higher in patients with TDT than that of healthy control. In addition, 1 (2.86%) TDT patient had hypocalcaemia and 12 (34.29%) had hyperphosphatemia. In conclusion of this study, serum total calcium level decreased and serum inorganic phosphate and serum ferritin level increased in patients with TDT. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(2):97-100.